Learning Modifications Through Play Rope Games For Children's Gross Motor Skills in Students - Hasyim Hasyim (STKIP Muhammadiyah Kuningan, 2021)
This study aims to determine the modification of learning through games for students before and after being given treatment in jumping rope games and whether there is an effect of improving learning through jumping rope games on children's gross motor skills in students. This type of research is pre-experimental research. The population in this study was the total number of students totaling 20 students in a class I Elementary School Takkalasi, Barru district, and the sample used was class I which amounted to 20 students with purposive sampling technique. Data collection techniques through observation, tests, documentation. Data analysis used Wilcoxon's difference test. The results of children's gross motor skills before being treated in the form of jumping rope game modification activities showed that of the 20 total children, 0% were in the developing category as expected, 90% were in the starting to develop variety, and 10% were in the undeveloped class, that motor skills Children's roughness after being treated in the form of a modified jumping rope game shows that of the 20 total children, 85% are in the developing category as expected, 15% are in the starting to develop variety, and 0% are in the undeveloped category.